2010
DOI: 10.1039/c0an00283f
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive paper dipstick sensors for acetylcholinesterase inhibitors based on sol–gel/enzyme/gold nanoparticle composites

Abstract: A bioactive paper-based colorimetric "dipstick" bioassay is reported that is based on acetylcholinesterase (AChE) catalyzed enlargement of gold nanoparticles that are co-entrapped with the enzyme in a sol-gel based silica material that is coated on a functionalized paper substrate. Test solutions containing acetylthiocholine (ATCh) and a Au(III) salt are spotted over the sensing area of the bioactive test strips containing small (3 nm diameter) primary gold nanoparticles (AuNP). Biocatalyzed hydrolysis of ATCh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 41 publications
0
59
0
1
Order By: Relevance
“…In search of alternative technological solutions, bioactive paper-based materials are being developed with the aim of detecting toxins in food packaging (Luckman & Brennan, 2010). The operating principle of this material consists in producing rapid colorimetric detection of one or more analytes simultaneously.…”
Section: Papermentioning
confidence: 99%
“…In search of alternative technological solutions, bioactive paper-based materials are being developed with the aim of detecting toxins in food packaging (Luckman & Brennan, 2010). The operating principle of this material consists in producing rapid colorimetric detection of one or more analytes simultaneously.…”
Section: Papermentioning
confidence: 99%
“…One proposal is combining assay reagents with sol-gel materials to immobilize reagents on paper. [64][65][66] In this way, Hossain et al developed a paper-based sensor which can detect organophosphate pesticides of nanomolar quantities in milk or lettuce by color changing. 65 Another proposal is using gold nanoparticle (AuNP) based colorimetric detection which can dramatically improve both the sensitivity and the specificity of detection.…”
Section: The Current Limitation Of Paper-based Microfluidic Devicesmentioning
confidence: 99%
“…82 In other examples, pH changing polyaniline-poly(sodium 4-styrenesulfonate) (PANI:PSS) NPs have been used to detect concentrations of amine vapors by monitoring the change in color to blue for basic pH environments. 83 Chaiyo et al detected Cu 2+ by measuring the change in color of Ag nanoplates in the presence of thiosulfate from pink to colorless on paper due to catalytic etching.…”
Section: ·1 Optical and Fluorescence Based Detectionmentioning
confidence: 99%
“…105 Luckham et al deposited enzyme/NP composites on paper to detect the acetylcholinesterase inhibitor paraoxon which is found in insecticides and nerve gases. 82 Ying et al reported an immunosensor for the detection of Escherichia coli (E. coli). Graphene paper was decorated by AuNPs through one-step electrodeposition and E. coli was immobilized on the surface using biotin-streptavidin chemistry.…”
Section: +mentioning
confidence: 99%